THE USE OF STUDENT TEAM ACHIEVEMENT DIVISION (STAD) TECHNIQUE TO IMPROVE STUDENTS’ READING COMPREHENSION ON EIGHTH GRADE OF SMP AL-HIDAYAH MALANG - Siti Aisyah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
ABSTRACT: Reading is one of the based skills which are practically activity for the learners to learn in school or through life. Besides, all of the subjects need reading skill to develop students’ ability in academic because reading is the fundamental. The objective of this study was to improve students’ reading comprehension of recount text by using STAD technique for the eighth grade students of SMP Al- Hidayah Malang. The problem investigated in this study was how the researcher improved students’ reading comprehension of recount text through STAD technique. The problems found are: 1) Most students got difficulties to find the information about the text, 2) They found difficulty to identify main idea, 3) They did not know about the meaning of the text.            The research design used in this study was Classroom Action Research (CAR) in which to identify and solve the problem on students’ reading comprehension. The subject of this research was eighth grade students of SMP Al-Hidayah Malang. The researcher chose class eight A (VIII A) with the total number of the students are 26 students. In this research there were 6 meetings: 1 meeting for pre-test, 4 meetings for research implementation in teaching learning English by using STAD and 1 meeting for post-test. The instruments used in this study were field note and test including pretest and posttest. In Classroom Action Research there are four procedures consist of planning, acting, observing and reflecting.        The results of this study indicate that the criteria for success of this study are 60% of the total participants as research subjects must obtain a minimum criterion for learning mastery (KKM) of 70, there are 80% of students who have achieved the criteria of success. The number of students who reached the minimum criteria for mastery learning (KKM) increased from 9 students to 19 students. It means that STAD technique can improve students’ reading skill on eighth grade students of SMP Al-Hidayah Malang.Based on the research finding, it can be concluded that using Student Team Achievement Division (STAD) technique in reading comprehension is successful since the criteria of success is achieved. The researcher suggests for the future researchers who will conduct similar study to apply the technique on different grades, levels of education and different skills. Keywords: improving reading comprehension, reading comprehension, and STAD (Student Team Achievement Division)